An analysis of the suitability of a low-cost eye tracker for assessing the cognitive load of drivers. (April 2018) - Čegovnik, Tomaž; Stojmenova, Kristina; Jakus, Grega; Sodnik, Jaka
Abstract: This paper presents a driving simulator study in which we investigated whether the Eye Tribe eye tracker (ET) is capable of assessing changes in the cognitive load of drivers through oculography and pupillometry. In the study, participants were asked to drive a simulated vehicle and simultaneously perform a set of secondary tasks with different cognitive complexity levels. We measured changes in eye properties, such as the pupil size, blink rate and fixation time. We also performed a measurement with a Detection Response Task (DRT) to validate the results and to prove a steady increase of cognitive load with increasing secondary task difficulty. The results showed that the ET precisely recognizes an increasing pupil diameter with increasing secondary task difficulty. In addition, the ET shows increasing blink rates, decreasing fixation time and narrowing of the attention field with increasing secondary task difficulty. The results were validated with the DRT method and the secondary task performance. We conclude that the Eye Tribe ET is a suitable device for assessing a driver's cognitive load. Highlights: Users were asked to drive safely in a driving simulator. Cognitive load was induced with the n-back secondary task and detected with the standardized DRT method. Pupil size increases with increasing cognitive load. EyeTribe eye tracker is suitable for measuring cognitive load. Pupil size tracking is an alternative to standardized methods of assessing cognitive load.